3D-printing polymer-based permanent magnets. (5th September 2018) - Domingo-Roca, R.; Jackson, J.C.; Windmill, J.F.C.
Abstract: Production of permanent magnets is a complex process that implies very specific machinery able to perform very specific actions. Even though this problem has been approached by extrusion-based three-dimensional printing techniques, the resulting parts either have not been fully characterized or present low-resolution outputs. In this study we use the stereolithography three-dimensional printing technique to address this problem and demonstrate that it is possible to develop high-resolution polymer-based permanent magnets. We report an in-depth magnetic characterization of the produced materials, including magnetization of saturation, coercivity, magnetic relative permeability, magnetic behaviour, type of interaction between particles, and magnetic domain orientation. We have further demonstrated that this orientation can be re-arranged. Obtaining contrasting properties of the developed materials opens the possibility of developing personalized, high-resolution devices that can be used in a wide range of fields such as micro-robotics, biotechnology, biomedicine, and medical science among many others. Graphical abstract: Unlabelled Image Highlights: 3D-printing polymer-based permanent magnets are presented. High-resolution devices can be developed with an accuracy of 50 μm. Development of 3D-printed magnets with different magnetic properties has been demonstrated. Such materials can be combined to fulfil user needs depending on the application.